2017
DOI: 10.1158/1055-9965.epi-17-0092
|View full text |Cite
|
Sign up to set email alerts
|

Making the Case for Investment in Rural Cancer Control: An Analysis of Rural Cancer Incidence, Mortality, and Funding Trends

Abstract: Estimates of those living in rural counties vary from 46.2–59 million, or 14–19% of the U.S. population. Rural communities face disadvantages compared to urban areas, including higher poverty, lower educational attainment, and lack of access to health services. We aimed to demonstrate rural-urban disparities in cancer and to examine NCI-funded cancer control grants focused on rural populations. Estimates of five-year cancer incidence and mortality from 2009–2013 were generated for counties at each level of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
268
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 288 publications
(273 citation statements)
references
References 36 publications
4
268
1
Order By: Relevance
“…[13][14][15][16][17] The sum of the total number of cases and the total population were calculated by state-county code and time period. The patient population was classified into urban and rural categories with the Rural-Urban Continuum Code (RUCC), a variable available in the SEER database.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17] The sum of the total number of cases and the total population were calculated by state-county code and time period. The patient population was classified into urban and rural categories with the Rural-Urban Continuum Code (RUCC), a variable available in the SEER database.…”
Section: Discussionmentioning
confidence: 99%
“…First, the main effect between urbanicity and cancer was reversed: breast cancer incidence was higher, while cervical cancer incidence was lower, in more urban versus more rural areas (Blake et al, 2017; Singh, 2011). Second, in complex mediation analysis, only SES and primary care provider density mediated the relationship between urbanicity and cancer incidence; neither percent non-Hispanic white nor Pap screening rate contributed to the ecological associations (although Pap screening rate did mediate the association in the preliminary models).…”
Section: Discussionmentioning
confidence: 99%
“…However, the burden of these cancers is not distributed equally across the United States: breast cancer incidence is higher, and cervical cancer incidence is lower, in urban areas compared to rural areas (Fogleman, Mueller, & Jenkins, 2015; Singh, 2011). One recent study found that, compared to rates in rural areas, breast cancer incidence rates were 9% higher in urban areas and cervical cancer incidence rates were 15% lower in urban areas (Blake, Moss, Gaysynsky, Srinivasan, & Croyle, 2017). Contrasting the associations of these cancers with potential local influences on health, such as sociodemographics (Pruitt, Shim, Mullen, Vernon, & Amick, 2009; Singh, Williams, Siahpush, & Mulhollen, 2011) and healthcare factors (Belasco, Gong, Pence, & Wilkes, 2014; Doescher & Jackson, 2009), can inform interventions aiming to reduce urban/rural disparities in cancer outcomes and improve overall population health (Wells & Horm, 1998).…”
Section: Urban/rural Differences In Breast and Cervical Cancer Incidementioning
confidence: 99%
“…Compared to their urban counterparts, US residents who reside in rural settings face an increased risk of premature mortality and health problems such as coronary heart disease, type 2 diabetes, obesity, and numerous types of cancer (including cervical, colorectal, kidney, and lung cancer) . Many of these health challenges have been linked to insufficient physical activity (PA) levels, and it may be that some of the elevated burden of morbidity and premature mortality afflicting rural communities is attributable to lifestyle factors such as lower PA levels .…”
mentioning
confidence: 99%